Fundatio Orzełkoviana. A Contribution to the History of Scholarship Foundations in Polonia Maior During the Old Polish Period - Nowicki, Michał (Biuletyn Historii Wychowania, 2018)
Most of articles on patronage in Greater Poland from the 16th to the 18th century concerns a direct dependence between the patron and the client. Thus, the present work concentrates on a specific kind of patronage – scholarship foundations, which are only briefly mentioned in historiography. Some of them are not known. “Fundatio orzelkoviana” serves as an example here to show the need for detailed relevant case studies to supplement the available data. Founded by Marcin Orzeł in 1566, the foundation existed for many years and helped young people to achieve academic education. Ius patronatus and control of the foundation was assigned to the Catedral Chapter of Poznań. Admittedly, this Chapter was interested in keeping the foundation in good condition, e. g. by being aware of economic and financial factors influencing the foundation and by carrying out the recovery in debts, be it rents or fees. The source material for the present discussion comes from the Main Archive for Poznań Archdiocese (mainly the acts of the Cathedral Chapter of Poznań, Consistory Court and the canonical visitation of Bishop Tholibowski).